1997
DOI: 10.1515/jaots-1997-0212
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Plasma Techniques for the Reduction of Volatile Organic Compounds in Air Streams: A Critical Review

Abstract: This paper critically reviews the non-thermal plasma techniques for reduction of volatile organic compounds (VOC) in air streams. The currently used technologies fall into two categories: those based on nonthermal plasma generated from various forms of corona discharge and those exploiting high energy electron beams. Relative advantages and disadvantages of non-thermal plasma and conventional techniques are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…(3a-b): Arrhenius function determined for a value of total density at 1 bar and 50°C using data from (a): [40] or from (b): [41]. (4): estimated reaction, unknown coefficient…”
Section: Ozone and Nitrogen Oxides In N 2 /O 2 Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…(3a-b): Arrhenius function determined for a value of total density at 1 bar and 50°C using data from (a): [40] or from (b): [41]. (4): estimated reaction, unknown coefficient…”
Section: Ozone and Nitrogen Oxides In N 2 /O 2 Mixturesmentioning
confidence: 99%
“…However, important energy consumption is needed in the case of important flows and/or low VOC concentration. Amongst alternative techniques presently under investigations, non-thermal equilibrium plasmas at atmospheric pressure are the subject of a great amount of researches [3][4][5][6][7]. Moreover it has been demonstrated that the combining of a non-thermal electrical discharge and a catalyst deposited on various supports such as honeycomb monoliths or pellets, can improve the efficiency of conversion processes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of diluted VOCs by applying NTP is of particular importance from the point of energy saving [5] [3,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to more strict environmental laws, many industries are looking for an effective technique for VOC-treatment. The recently developed techniques based on non-thermal plasmas (plasma = partially ionized gas) are an alternative for conventional methods like thermal incineration, catalytic oxidation and adsorption [4] [5]. The main advantage of a non-thermal plasma technique is that the available energy is added selectively to the plasma electrons.…”
Section: Introductionmentioning
confidence: 99%